2020
DOI: 10.3390/w12112969
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study of the Influence of Channel-Scale Secondary Circulation on Mixing Processes Downstream of River Junctions

Abstract: A rapid downstream weakening of the processes that drive the intensity of transverse mixing at the confluence of large rivers has been identified in the literature and attributed to the progressive reduction in channel scale secondary circulation and shear-driven mixing with distance downstream from the junction. These processes are investigated in this paper using a three-dimensional computation of the Reynolds averaged Navier Stokes equations combined with a Reynolds stress turbulence model for the confluenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…As mentioned before, we infer that the flow with a large velocity near the surface rushed to the right bank and abruptly changed its direction to the left (Figure 5a), creating such anti‐clockwise cell. The topographic steering near the bed, for example, the swell in the middle of CYP6, may also play a role in generating this cell (Lyubimova et al., 2020). At CYP4 and CYP5 a deep scour hole, 6 m deeper than that at CYP3 and 3 m deeper than that at CYP6, was observed.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned before, we infer that the flow with a large velocity near the surface rushed to the right bank and abruptly changed its direction to the left (Figure 5a), creating such anti‐clockwise cell. The topographic steering near the bed, for example, the swell in the middle of CYP6, may also play a role in generating this cell (Lyubimova et al., 2020). At CYP4 and CYP5 a deep scour hole, 6 m deeper than that at CYP3 and 3 m deeper than that at CYP6, was observed.…”
Section: Resultsmentioning
confidence: 99%
“…The dynamics and structure of the MI become even more complex once buoyancy starts playing an important role (Laraque, Guyot & Filizola 2009;Prats et al 2010;Lyubimova et al 2014Lyubimova et al , 2020Ramón et al 2014;Lewis & Rhoads 2015;Gualtieri, Ianniruberto & Filizola 2019;Gualtieri et al 2019;Horna-Munoz et al 2020). For sufficiently large density contrast between the incoming streams, the rates of mixing between the two streams were found to be quite different from the ones observed for cases with negligible density contrast (Horna-Munoz et al 2020).…”
mentioning
confidence: 94%
“…2010; Lyubimova et al. 2014, 2020; Ramón et al. 2014; Lewis & Rhoads 2015; Cheng & Constantinescu 2018; Gualtieri, Ianniruberto & Filizola 2019; Gualtieri et al.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the existence of secondary flow in bends, branching or confluence rivers also exist. erefore, Chen et al [13] and Lyubimova et al [14] found that while twin secondary circulations are found at channel confluence, their contribution to the mixing depends on their local positions with respect to the river streams, and the water depth drives the most rapid mixing and notably. omas et al [15] evaluated the influence of secondary flow disturbance on bifurcation evolution.…”
Section: Introductionmentioning
confidence: 99%